Pemanfaatan Limbah Tepung Tulang Sebagai Pupuk Organik Terhadap Produktivitas Hidroponik Fodder Jagung - Tri Ida Wahyu Kustyorini; Dimas Pratidina puriastuti Hadiani (Fakultas Peternakan Universitas Halu Oleo, 2024)
Abstract. Livestock productivity is influenced by three factors namely breed, feed and management. Animal feed costs on average reach 70% of production costs, so feed management must be done as well as possible. A common problem faced by farmers in Indonesia is limited land for planting forage, so an alternative is needed to fulfill forage by minimizing land use, namely one way with a hydroponic system. In recent years there has been increasing interest in using short growing duration feed cultivation technology known as fodder. Based on this, the purpose of this study was to determine the utilization of bone meal waste as organic fertilizer on productivity fodder corn. The materials in this study included corn seeds, bone meal and water. The method used is a field experiment using a Completely Randomized Design (CRD). The treatment in this study was the use of bone meal as organic fertilizer, where P0 (0%), P1 (5%), P2 (10%), and P3 (15%). Each treatment was repeated 4 times. The research variables included germination percentage, normal sprout percentage, fresh forage production, and dry matter production. The data obtained was analyzed using analysis of variance. Based on the results of statistical analysis, it was shown that the use of bone meal as organic fertilizer had a very significant (P<0.01) effect on germination percentage, normal sprout percentage, fresh forage production and dry matter production. Germination percentage, normal germination percentage, fresh forage production and dry matter production were highest in P2 treatment. The values of each variable in P2 are sequentially as follows: 97.75%, 91.35%, 709.60 grams and 140.93%. Based on the results, it can be concluded that the use of 10% cast flour as organic fertilizer gives the best value to the productivity of corn fodder hydroponically.